The Therapeutic Approaches for Hepatitis C Virus: Protease Inhibitors and Polymerase Inhibitors - Kwo, Paul Y. (The Korean Society of Gastroenterology; the Korean Society of Gastrointestinal Endoscopy; the Korean Association for the Study of the Liver; the Korean Society of Neurogastroenterology and Motility; Korean Association for the Study of Intestinal Diseases; Korean College of Helicobacter and Upper Gastrointestinal Research; Korean Society of Pancreatobiliary Diseases, 2011)
The current standard of care for hepatitis C infection is peginterferon/ribavirin (PegIFN/RBV). We are entering the era where direct-acting antiviral agents (DAAs) will be added to PegIFN/RBV, leading to higher sustained response rates in genotype 1 infected individuals. Currently DAAs are directed toward specific proteins involved in hepatitis C replication with NS3/NS4A protease inhibitors furthest in development. Telaprevir and boceprevir are both NS3/NS4a inhibitors that significantly improve sustained response when added to PegIFN and RBV. The hepatitis C virus (HCV) polymerase inhibitors are another promising DAA class. These molecules are divided into nucleoside/nucleotide polymerase inhibitors and nonnucleotide/nucleoside polymerase inhibitors. Nucleoside/nucleotide polymerase inhibitors have a high barrier to resistance and appear to be effective across a broad range of genotypes. Nonnucleoside polymerase inhibitors have a lower barrier of resistance and appear to be genotype specific. Preliminary data with these compounds are also promising. A third class, NS5A inhibitors, has also shown potent HCV RNA suppression in preliminary studies as monotherapy and with PegIFN and RBV. Combinations of these agents are also entering clinical trials and indeed a preliminary report has demonstrated that the combination of an NS3/4A protease inhibitor and NS5B polymerase inhibitor can effectively suppress virus in genotype 1 individuals. Future studies will concentrate on combinations of direct-acting antiviral agents without and with PegIFN and RBV. Clinicians will need to be familiar with managing side effects as well as resistance as we enter this new era.